History of human genetics : aspects of its development and global perspectives - Petermann, Heike; Harper, Peter S.; Doetz, Susanne, 1966- (Springer, 2017)
This book provides a unique overview of exciting discoveries and surprising developments in human genetics over the last 50 years. The individual contributions, based on seven international workshops on the history of human genetics, cover a diverse range of topics, including the early years of the discipline, gene mapping and diagnostics. The value of genetic counseling as an important subfield of medical genetics is also discussed.
Keywords: Human genetics -- History.; elektronické knihy; electronic books